Effect of Genetic Counseling and Testing for BRCA1 and BRCA2 Mutations in African American Women: A Randomized Trial - Halbert, C.H. (S. Karger AG, 2010)
BACKGROUND: Limited empirical data are available on the effects of genetic counseling and testing among African American women. OBJECTIVE: To evaluate the effects of genetic counseling and testing in African American women based on different levels of exposure: (a) women who were randomized to culturally tailored (CTGC) and standard genetic counseling (SGC) to women who declined randomization (non-randomized group), (b) participants and non-participants in genetic counseling, and (c) BRCA1 and BRCA2 (BRCA1/2) test result acceptors and decliners. DESIGN: Randomized trial of genetic counseling conducted from February 2003 to November 2006. MEASURES: We evaluated changes in perceived risk of developing breast cancer and cancer worry. RESULTS: Women randomized to CTGC and SGC did not differ in terms of changes in risk perception and cancer worry compared to decliners. However, counseling participants had a significantly greater likelihood of reporting reductions in perceived risk compared to non-participants (p = 0.03). Test result acceptors also had a significantly greater likelihood of reporting decreases in cancer worry (p = 0.03). However, having a cancer history (p = 0.03) and a BRCA1/2 prior probability (p = 0.04) were associated with increases in cancer worry. CONCLUSIONS: Although CTGC did not lead to significant improvements in perceived risk or psychological functioning, African American women may benefit from genetic counseling and testing. Continued efforts should be made to increase access to genetic counseling and testing among African American women at increased risk for hereditary disease. But, follow-up support may be needed for women who have a personal history of cancer and those with a greater prior probability of having a BRCA1/2 mutation.